Analysis of Media Needs for Dance Learning for Deaf Students Based on Interactive Multimedia - Widyahety, Indah; Sunardi, Sunardi; Yuwono, Joko (Angstrom Centre of Education, 2022)
This study aims to analyze the essential needs in the development of digital media for learning the art of dance for deaf students in special schools. This research design uses a descriptive study approach. The population of this research is all dance teachers who teach deaf students at Special Schools (SLB) Central Java. The sampling technique used was the incidental sampling technique. The data collection technique used a questionnaire sent in google form format through WhatsApp media. Data analysis used a descriptive technique by measuring each item with percentage criteria. The results of the study show that the expected digital media is interactive multimedia, with a duration of 15 to 20 minutes. The media can be stored and operated on all digital media. The content of the dance that is expected is a traditional dance. The media is equipped with a complete user manual.